Re-thinking International Students’ Voice in South-South Cooperation in Higher Education 关于发展中国家留学生在华学习体验的反思: An International Development Perspective 国际发展的视角 - Yuan, Tingting (Journal of International Students, 2020)
This article provides an initial reflection based on a recent qualitative study on China’s higher education and scholarship provision to international students from developing countries. The empirical data collected from focus groups reveal two emerging aspects of students’ overall experience: those of equality and sustainability. These two features fundamentally reflect China’s distinctiveness in its higher education provision in South-South Cooperation and its status in contemporary global political economy.文章从国际发展视角对一项近期进行的质性研究进行了阶段性的反思。该研究对获得中国奖学金的发展中国家在华留学生进行了访谈。初步研究结果将在华留学这个高等教育范畴内的实践和中国在南南合作中所做的贡献联系起来。本文旨在揭示留学生体验的两点鲜明特征，即在华留学的“平等性”和“可持续性”。而这两点特征也在根本上体现了中国提供的高等教育的特殊性和中国在当前国际政治经济中的角色和地位。